Changes in Dietary Intake After Metformin Treatment and Behavioral Weight Loss Intervention in Overweight or Obese Cancer Survivors: Results from a Randomized Clinical Trial (P05-029-19). (13th June 2019) - Li, Zhongyu; Mueller, Noel; Stephen, Juraschek; Yeh, Hsin-Chieh; Appel, Lawrence; Miller, Edgar R; Maruthur, Nisa
Abstract: Objectives: Metformin and behavioral weight loss are postulated to lower the risk of cancer development and recurrence in overweight/obese individuals. Few studies have compared dietary changes longitudinally associated with these interventions. This study aimed to investigate the effects of metformin treatment and coach-directed behavioral weight loss intervention on overweight/obese cancer survivors' food consumption, with an emphasis on fruits, vegetables, fiber, and fat intakes. Methods: Overweight and obese cancer survivors enrolled in the SPIRIT trial ( n  = 121) were randomized into three arms consisting of self-directed weight loss (control), coach-directed weight loss and metformin treatment. Fruit, vegetable and fat screeners were used to assess the diet of the participants at baseline, 3-month, 6-month, and 12-month visit. Linear regression models and Generalized Estimated Equations were performed in STATA 15.1 to analyze the associations between interventions and food consumption throughout the study. Results: Groups did not differ by sex (79% female), race (45% black) or age (mean 60 years). Metformin treatment was associated with decreased dietary fiber intake versus self-directed group (difference in slope β = −0.13, 95%CI: −0.01, −0.25; P  = 0.04) and versus coach-directed group (−0.130, 95%CI: −0.02, −0.24; P  = 0.02). After adjusting for baseline intake, participants assigned to metformin treatment consumed less dietary fiber daily than did participants in the self-directed (−2.0 grams, 95%CI: −0.47, −3.53; P  = 0.01) and coach directed groups (−1.54 grams, 95%CI: −0.12, −2.95; P  = 0.03) at the 12-month visit. Fruit and vegetable servings also decreased among participants in the metformin group versus non-metformin groups (difference at 12 months = −0.47 servings, 95%CI: 0.00, −0.94; P  = 0.05). Coach-directed weight loss reduced % calories from fat compared to self-directed (−1.5% P  = 0.03). Conclusions: Metformin treatment in overweight/obese cancer survivors was associated with reduced intake of fruits, vegetables, and dietary fiber. The unintended and negative changes of diet that could result in negative impacts on health in metformin users should be noticed in clinical practices and deserve further research. Funding Sources: Maryland Cigarette Restitution Funds and SKCCC. Supporting Tables, Images and/or Graphs: